SISTEM PENDUKUNG KEPUTUSAN PENENTUAN MINAT DAN BAKAT SISWA PADA SMKN 2 MUARO JAMBI: Decision support system, Weighted product (WP),Web - Huda Aminuddin, Fattachul; Sany, Ezrifal; Kahar, Novhirtamely (LP2M Universitas Nurdin Hamzah, 2019)
Decision support system is part of a computer-based information systems used to support decision making in an organization or company. Decision support systems can be generated by using several kinds of methods, one of which is a method of Weighted Product (WP). Weigthted Product is completion method using multiplication to connect the attribute value, where the value should be raised to advance with the relevant attribute weights. Input data used this system is input student data, alternative data input, data input criteria, and the input weighted values ​​for each criterion. Data output is in the form of alternative data report, data report criteria, report student data and reports majors. By using the method of Weighted Product (WP) is a web-based, it is expected the process of placement of students more effectively and efficiently so that students quickly get information about majors and majors also results in accordance with each student's ability. By using decision support system and database, the data of students or student majors values ​​can be stored in it, so if there is an error in inputting values ​​or student data, then the erroneous data can be corrected without having to re-input the value or student data.